Beta‐elemene inhibits breast cancer metastasis through blocking pyruvate kinase M2 dimerization and nuclear translocation. Issue 10 (25th July 2019) - Pan, Yanhong; Wang, Wei; Huang, Shuai; Ni, Wenting; Wei, Zhonghong; Cao, Yuzhu; Yu, Suyun; Jia, Qi; Wu, Yuanyuan; Chai, Chuan; Zheng, Qian; Zhang, Lei; et al.
Abstract: Pyruvate kinase M2 (PKM2), playing a central role in regulating aerobic glycolysis, was considered as a promising target for cancer therapy. However, its role in cancer metastasis is rarely known. Here, we found a tight relationship between PKM2 and breast cancer metastasis, demonstrated by the findings that beta‐elemene (β‐elemene), an approved drug for complementary cancer therapy, exerted distinct anti‐metastatic activity dependent on PKM2. The results indicated that β‐elemene inhibited breast cancer cell migration, invasion in vitro as well as metastases in vivo. β‐Elemene further inhibited the process of aerobic glycolysis and decreased the utilization of glucose and the production of pyruvate and lactate through suppressing pyruvate kinase activity by modulating the transformation of dimeric and tetrameric forms of PKM2. Further analysis revealed that β‐elemene suppressed aerobic glycolysis by blocking PKM2 nuclear translocation and the expression of EGFR, GLUT1 and LDHA by influencing the expression of importin α5. Furthermore, the effect of β‐elemene on migration, invasion, PKM2 transformation, and nuclear translocation could be reversed in part by fructose‐1, 6‐bisphosphate (FBP) and L‐cysteine. Taken together, tetrameric transformation and nuclear translocation of PKM2 are essential for cancer metastasis, and β‐elemene inhibited breast cancer metastasis via blocking aerobic glycolysis mediated by dimeric PKM2 transformation and nuclear translocation, being a promising anti‐metastatic agent from natural compounds.